Molecular dynamics simulation of the nanoindentation process in Cr/CrN and (Cr/CrN)2 thin films - Amaya Roncancio, Sebastian (2018)
Molecular dynamics (MD) simulations were carries out for studying the influenceof nanoindentation in the atomistic deformation mechanisms of Cr/CrN and(Cr/CrN)2 coatings with BCC and FCC crystalline structures for Cr and CrN,respectively. The Morse potential was employed in order to determine the atomicinteraction forces of the Cr-Cr and Cr-N atoms. A non-deformable potential solidsphere was implemented for determining the role of the nanoindenter. The OliverParr method (OP) was used to obtain the hardness and elastic modulus of the Cr/CrN and (Cr/CrN)2 layers, resulting in values of 18 and 20 GPa for Cr/CrN and (Cr/CrN)2, respectively. The Cheng method was used for correcting the hardness values obtained by the OP method. The Cheng correction showed higher hardness values since it avoids the influence of the scale effect. Regarding the elasticity modulus, Cr/CrN and (Cr/CrN)2 exhibited values of 217.86 GPa and 258.9 GPa, respectively. Simulations of the temperature influence on the hardness were carried out over a range of 300-1000 K. Results indicate that the hardness decreased as a function of the temperature.